Transformational leadership and sport commitment: a study of Iranian high schools' football teams - Sayebani, Hamid Reza; Yusof, Aminudin; Chee, Chen Soon; Hassan, Aminuddin (Universiti Putra Malaysia Press, 2015)
The aim of this study was to investigate the relationship between the transformational leadership style of Iranian high school coaches and the sport commitment of Iranian high school football players. This study also examined the effect of age and playing experience on athletes' sport commitment. A total of 270 football players were selected from 31 high school football teams in Iran using the simple random sampling procedure. Instruments of the study were the Multifactor Leadership Questionnaire (MLQ) (Avolio & Bass, 1995) and Sport Commitment Model Scale (SCMS) (Scanlan, Carpenter, Schmidt, Simons, & Keeler, 1993). The results of the study indicated that there is a positive and significant relationship between the transformational leadership style of coaches and sport commitment (r=.419, β=.478, ρ value=.001). In addition, the results also showed that there are no significant differences in sport commitment of football players of different ages (F=1.115, p value=0.330>0.05) and years of football experience (F=0.053, p value=0.948>0.05). Findings of this study suggest that the transformational leadership style is effective in enhancing the sport commitment of Iranian high school football players.